Early feminists of colonial India Sarala Devi Chaudhurani and Rokeya Sakhawat Hossain - Ray, Bharati (Oxford : Oxford University Press, 2013)
It presents a historical evaluation of Sarala Devi Chaudhurani and Begum Rokeya Sakhawat Hossain. It specifically determines the similarities and differences in the ideas and activities of these women from two different communities in colonial Bengal, Hindu-Brahmo and Muslim, and thus also sheds some light on contemporary Hindu and Muslim societies, their patterns of change during the colonial encounter, and the emergence among both the communities of a new generation of women.
Description based on online resource; title from home page (viewed on Jan. 3, 2013).
Keywords: Chaudhurani, Sarala Devi, -- 1872-1945.; c; Feminists -- India -- Bengal; Feminism -- India -- Bengal -- History; Bengal (India) -- Social conditions